Effect of Intraumbilical (IU) Vein Oxytocin Injection on Duration of Third Stage of Labour: A Comparative Study: Intraumbilical Vein Oxytocin Injection on Duration of Third Stage of Labour - Sabir, Anila; Haider, Shazia; Ghaffar, Sadia; Sattar, Shaneela; Maryam, Sana; Aamir, Ayesha; Kanwal, Sibgha; Zahid, Hafiza Maryam; Kanwal, Seep (Pakistan Journal of Health Sciences, 2024)
Effective management for reducing the duration of 3rd stage of labour can prevent serious complications such as post-partum hemorrhage. Objective: To evaluate the effect of intraumbilical venous oxytocin injection compared to placebo on reducing the duration of the third stage of labour in normal vaginal deliveries. Methods: In this quasi-experimental study, 100 pregnant female fulfilling the selection criteria were included from the Obstetrics and Gynecology Department of Sharif Medical and Dental City Hospital, Lahore. Informed consent was attained from participants. Participants were divided into 2 groups. In Group A, the female was given intraumbilical oxytocin and in Group B, a placebo (normal saline) was used. All female was followed up till delivery of the fetus and time was noted from delivery of the fetus to the placenta. Data were analyzed using SPSS version 26.0. Results: In Group in. Intraumbilical oxytocin, duration of 3rd stage of labour was less than 3.68 ± 1.49 minutes as compared to placebo group 7.02 ± 2.85 minutes (p<0.01). Data stratification concerning age, gestational age and parity also showed a significant difference of 3rd stage duration among groups with p<0.01. Conclusions: It was concluded that intraumbilical oxytocin was found to be useful in decreasing the third stage of labour duration. Its use may help prevent cases of prolonged third stage, which could otherwise lead to adverse outcomes. These findings support the potential clinical benefits of IU oxytocin in the third stage of labour.